PENGARUH SUDUT KEMIRINGAN PLAT TERHADAP KOEFISIEN PERPINDAHAN PANAS KONVEKSI BEBAS - Sudargana, Sudargana (ROTASI, 2001)
In general literature, there is no Nuselt Number formula on several angle flat plate at free convection. Thereare the local Nuselt Number formulas for forced convection heat transfer in cross flow on pipe. While in the practicaltecnology as in the boiler, we find pipe or plat at in angle. The aim of this research is to discript the influence of angleof plate to Nuselt Number for free convection heat transfer. The hot fluid is steam and cold fluid is water.Steam flow at low Renold Number or laminair flow (pressure difference about stagnation and static prssure at1 cm coloum water). We asume that thermal conducticity for plate material is known (from conduction table). From theseries heat transfer, convection on hot fluid, conduction on plate material and convection on cold fluid, we can find thefree convection at hot and cold fluid. Than we can calculate Nuselt Number at both free convection. The form of freeconvection at this result and theoritical are similar with a little deviation.